IMPLEMENTASI MODEL MEDIA CROSSWORD PUZZLE BERGAMBAR ALTERNATIF MEDIA PEMBELAJARAN SELAMA PANDEMI COVID-19 DI MADRASAH IBTIDAIYAH - Baharudin Baharudin; Ida Fiteriani; Sri Sukasih; Citra Wulan Sari (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2022)
The implementation of Picture Crossword Puzzle (MCP-G) media model is an alternative to making it easier for teachers to deliver durring pandemic COVID-19. MCP-B can create a more pleasant learning atmosphere and foster active student participation. This study aims to produce learning media products that can support thematic motivation and learning outcomes for fourth-grade students of MI. Product development refers to ADDIE design. The products developed are lesson plans, worksheets, learning media and motivational instruments and learning outcomes tests. The product development stages start from the initial-late analysis, student analysis, material analysis, task analysis, learning objectives analysis, method selection, format selection, expert validity, limited trials, field trials and revisions. The research data was sourced from expert validation sheets, student motivation observation sheets, teacher ability observation sheets in managing learning from the practical side and implementation of MCP-G learning media. The results show that the MCP-B model is feasible and effective to use in supporting motivation and thematic learning outcomes with the theme: